Petrology dataset of Pliocene-Pleistocene sediments in northeastern Slovenia - Mencin Gale, Eva; Kralj, Polona; Trajanova, Mirka; Gale, Luka; Skaberne, Dragomir (Geologija, 2024)
This is a dataset of petrological analysis of Pliocene-Pleistocene fluvial sediments from 14 gravely samples from the Slovenj Gradec, Nazarje, Celje and Drava-Ptuj Basin (northeastern Slovenia), collected for clast lithological analysis. The petrological analysis includes description of 155 thin sections of metamorphic, volcanic, volcaniclastic, clastic and carbonate rocks. This dataset provides grounds for determining the provenance of these gravel deposits, revealing possible resedimentation processes, and serves as a tool for drainage network interpretation in the Pliocene-Pleistocene.